Enhancing student empowerment through extracurricular activities: a study of NAMA foundation supported schools in Indonesia, Kyrgyzstan and Tanzania - Ahmed, Mahfooz; Mansour, Khiati; Al-Hidabi, Dawood Abdulmalek Yahya (International Institute for Muslim Unity (IIMU), International Islamic University Malaysia, 2024)
This study examines the impact of extracurricular activities on student empowerment in NAMA Foundation-supported schools across Indonesia, Kyrgyzstan, and Tanzania. The research tracks progress by utilising data from 2022 school evaluations compared to a 2021 baseline. It evaluates the effect of NAMA interventions on student development of personal skills aligned with their Theory of Change. A longitudinal survey methodology was employed to investigate the effects of NAMA’s intervention programs on student empowerment through extracurricular activities. Data was collected by a team of 23 trained NAMA assessors using an evaluation form focusing on Student Life, Learning Success, and Culture and Values during 2021 and 2022 school evaluations across 63 NAMA-supported schools. The study reveals positive impacts of the NAMA intervention, linking consistent extracurricular activity participation to higher educational attainment and improved interpersonal competence in students. These findings contribute to understanding how extracurricular activities can empower students and foster holistic development within supported institutions.